2013
DOI: 10.1080/00220388.2012.700397
|View full text |Cite
|
Sign up to set email alerts
|

The School Governance Environment in Uttar Pradesh, India: Implications for Teacher Accountability and Effort

Abstract: The school governance environment is an important determinant of schooling quality and thus of development. This paper explores how school governance is influenced by teacher unions and teacher politicians by presenting evidence on the political penetration of teachers, the activities of teacher unions and the stances of teachers' organisations on various decentralisation and accountability reform proposals over time. It asks how student achievement varies with teachers' union membership and political connecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…Furthermore, Kingdon and Muzammil [18] (2012) reviewed the dynamics of educational organizations. Kingdon and Muzammil [18] argue that governance in educational organizations demands fair rewards, appropriate incentives, and professional development opportunities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Kingdon and Muzammil [18] (2012) reviewed the dynamics of educational organizations. Kingdon and Muzammil [18] argue that governance in educational organizations demands fair rewards, appropriate incentives, and professional development opportunities.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Furthermore, Kingdon and Muzammil [18] (2012) reviewed the dynamics of educational organizations. Kingdon and Muzammil [18] argue that governance in educational organizations demands fair rewards, appropriate incentives, and professional development opportunities. These efforts will give teachers the chance to achieve competitive advantage in themselves and then be accountable for their performance in a transparent and accountable manner to leaders, parents of students, the community, and other stakeholders [18].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Kingdon (2008) reported that in Uttar Pradesh, India, recurrent per-pupil expenditures in private schools were only 41 percent of what public schools were spending and attributed most of the difference to teacher salaries, the largest cost component. Evidence from India further suggests that the cost differential may have increased dramatically over time: while in the mid-1990s, private teacher salaries were about 40-50 percent of government teacher salaries, by the early 2000s they were only about 20 percent (Kingdon and Muzammil 2013). Introduced in 2005, the Foundation Assisted School (FAS) program administered by the Punjab Education Foundation (Pakistan) provides conditional cash subsidies to low-cost private schools in order to offer private school opportunities for children from low-income households and raise the level of learning in those schools.…”
Section: Cost-effectiveness Of Private Schoolsmentioning
confidence: 99%
“…Even if student numbers fall, the school still gets its full grant; in consequence, PTRs fall and perpupil spending rises. In a survey of 10 government-funded schools in Lucknow district, Uttar Pradesh, Kingdon and Muzammil (2010) found that the PTR ratio had fallen to 9.7, but teacher unions and politicians supported teachers who refused to be deployed to local schools with more students.…”
Section: Improving Incentives For Schoolsmentioning
confidence: 99%
“…Andrabi et al (2007) document that wages for private school teachers in rural Punjab, Pakistan, were up to 5 times lower than for government school teachers. Kingdon and Muzammil (2012) suggest a worsening trend: in Uttar Pradesh, India, government school teachers were paid 2.5 times the wages of unaided school teachers in the early 1990s, 5 times in the early 2000s, 12 times in 2008, and most probably up to 24 times thereafter with the Sixth Pay Commission's salary recommendations in effect. Private school teachers are usually hired and paid competitively against the local labor market, and likely to be women who would 20 face social and/or commuting barriers in traveling to work outside of the local community.…”
mentioning
confidence: 99%